PEMBELAJARAN TARI LEGONG BAPANG SABA UNTUK MENINGKATKAN PEMAHAMAN NILAI PENDIDIKAN SOSIAL DI SANGGAR TARI BALI ASMARANDANA - Sang Ayu Made Diah Sri Anjani, - (2023)
This study analyzes the value of social education in the Legong Bapang Saba dance which will then be used as teaching material in increasing the understanding of the value of social education for children in Asmarandana Studio as a non-formal educational institution. In the Legong Bapang Saba dance, the researcher examines and analyzes the value of social education for children using the Grand Theory of Constructivism by Vigotsky and uses Ethnochoreology theory to examine the value of social education contained in the range of motion and finds 4 variations of motion which are characteristic according to the value of social education (self-confidence). , social interaction, and cooperation) including: Agem ngandang ngenjat dagu, Nyeleog, Tanjek apisan, dan ngelukun.. The learning model used in the implementation of this learning uses cooperative learning type Student Teams Achievement Division. This research method is included in the mixed method paradigm, namely descriptive analysis and experiment with a pre-experimental design "one group pre-test posttest". The data obtained were sourced from observations, literature review, documentation studies, questionnaires and were analyzed through the T test. The indicators of the researcher's achievement consisted of 3 values, namely: Confidence, social interaction, and cooperation. While the average value of the self-confidence character pretest obtained is 4.4, the social interaction character obtained is 4.7 The average value of the cooperation character pretest obtained is 4.16 then the results of the calculation of the T test in Excel explain that the results of the t stat it is min (-) so it can be concluded that Ha is accepted and Ho is rejected, meaning that there are differences and changes in the conditions of students before and after being given treatment Keywords: Legong Bapang Saba, Mix Methode, Cooperative Learning, Student Teams Achievement Division, Social Education Value.